SWOT Analysis At Inspektorat Of Kota Payakumbuh Through Grounded Theory Research Methods - Elfira, Renti; Oki, Helzulmita; Kettipusem, Sri Polya; Heikal, Jerry (Business and Investment Review, 2023)
To carry out its role and function as a Government Internal Supervisory Apparatus (APIP), the Payakumbuh City Inspectorate requires a management strategy that will become a reference in achieving performance. The strategy is determined through a SWOT analysis. Where in the SWOT analysis process is carried out through research using qualitative research methods with a grounded theory approach as a model in research. Researchers collected data using semi-structured interviews, field observations, document analysis and literature studies. The analysis performed included open-coding of the data to identify categories and themes; axial-coding to link categories and themes; and selective-coding to identify core themes. Based on the research, there are 4 (four) themes, namely the theme of strengths, weaknesses, opportunities, and threats. Where Weakness (weakness) is an internal factor that has the greatest influence on the performance of the Payakumbuh City Inspectorate with a score of 16 points. Followed by the theme of threats (threats) 12 points, then strengths (strength) 8 points, and finally opportunity (strength) 5 points. The strategic policy that can be carried out by the Payakumbuh City Inspectorate when viewed from the results of the SWOT analysis is to overcome the weaknesses that are owned because the score is the highest, and is an internal factor that can still be interpreted by the Inspectorate. Things that can be done include budgeting for the provision of adequate facilities and infrastructure and assigning APIP to attend training and technical training for 120 hours per year.